The Influence Of Work Discipline And Compensation On Employee Performance At The Office Of The Ministry Of Religion Of West Java Province - Jihan Nabila Rajwaa Indah Syamsina; Ratna Komala Putri (Cita konsultindo, 2024)
Based on internal data at the West Java Ministry of Religious Affairs, there are problems related to employee performance because it has decreased every year. The decline in employee performance requires serious attention so that it can still achieve maximum targets. Work discipline and compensation are factors that can affect employee performance. This study aims to examine the influence given by work discipline and compensation on employee performance at the Regional Office of the Ministry of Religion of West Java Province. The approach method used is descriptive analysis and quantitatively through a questionnaire involving 126 employees who work at the Regional Office of the Ministry of Religion of West Java Province. The results of the analysis using SPSS v23 software show that there is a positive and significant influence given by work discipline on employee performance, compensation on employee performance and work discipline and compensation together have a significant effect on employee performance. The suggestions given include increasing awareness of employee attendance and return, and agencies need to fight for basic salaries in order to meet the basic needs of employees with the aim of improving performance and minimizing the decline in employee performance.